Assessing the Viability of a Small Micro-Enterprise of an Urban Farming Group in Bausasran Village, Yogyakarta, in Developing a Vegetable-based Noodle Products - Luthfi Ash Shiddiqie Habib; Putra Ryan Anugrah; Wiranata Ardi; Ariyanto Teguh (BIO Web of Conferences, 2023)
Gemah Ripah Farmer Group, located in Bausasran Village, Danurejan District, Yogyakarta City, is one of the small farmer groups that have successfully practiced urban farming. The group grows vegetables and fruits. The harvest is then sold directly to consumers or distributors. To increase the economic value, the group plans to start a small micro-scale dry noodle product business by utilizing their cultivation results. In business planning, an economic feasibility analysis is required. This study aims to determine the business feasibility with the indicators of Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Added value analysis with Hayami Method. This study simulates two business scenarios for dry noodle production, namely own production and third-party production with three variables of production capacity analyzed, namely 760, 950, and 1140 units/month. The results of this study show that self production scenario with a production capacity of 1140 pieces/month produces a higher level of feasibility with a value of NPV, IRR and payback period of IDR 42,038,344, 59% and 1.88 years respectively. Value-added analysis provides added value in the self-production scenario of IDR 55,527/kg at the production rate of 1140 units/month.